Gamified Massive Open Online Course to Enhance Learner Engagement and Learning Outcomes - Pratama, Rikky Ihza; Retnowardhani, Astari (JTP - Jurnal Teknologi Pendidikan, 2025)
The use of Ruangguru app significantly increases learner engagement in the learning process. Ruangguru app uses gamification method in its learning design. In this app, there are features such as point system, rewards, and levels that are designed to increase learner motivation and engagement in the learning process. In addition, there are also game elements such as challenges, missions, and leaderboards designed to make the learning process more interesting and interactive. These features provide a more enjoyable learning experience for participants and encourage them to be more active in learning. Many MOOCs (Massive Open Online Course) use gamification methods in their learning design. A unique feature of Ruangguru app is the use of animated characters as learning guides. These animated characters are designed with local characteristics, so that participants can more easily identify and feel familiar with the characters. The method used in this research is quantitative method using data processing with SEM PLS software. The results showed that there was an influence of MOOC Gamification on participant engagement and there was also an influence between MOOC Gamification on participant learning outcomes.